RANCANG BANGUN MEDIA DUTA INDONESIA DALAM MENINGKATKAN WAWASAN NUSANTARA - Minto Santoso; Mochamad Yusuf Zen (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Archipelago insight is an important and fundamental part for every citizen especially for students to understand urgency of civic education in life of nation and state. The low of interest in student learning can be improved through learning media, such as experimental devices, simulations and games. Approachment of this research uses Research and Development method with the end product is game application named Duta Indonesia (Dadu and Peta Indonesia). This research is divided into two phases. The first stage is game development and the second is testing. Game Duta Indonesia designed and built in the form of software inserted with questions about the concept of insight archipelago. The game is designed using constract2 programming software supported by corel draw image processing program. This game is tested to FKIP UNISBA students who take the course of state education. From the results of experiments conducted 84% of students feel happy and have no trouble using this game and add insight their nationality. So it can be concluded that the research product is easy to apply, able to stimulate students to learn, and improve student knowledge of insights archipelago. Keywords: software, Duta Indonesia media application, Archipelago insight